2008
DOI: 10.1038/nm.1897
|View full text |Cite|
|
Sign up to set email alerts
|

Dcx reexpression reduces subcortical band heterotopia and seizure threshold in an animal model of neuronal migration disorder

Abstract: Disorders of neuronal migration can lead to malformations of the cerebral neocortex that greatly increase the risk of seizures. It remains untested whether malformations caused by disorders in neuronal migration can be reduced by reactivating cellular migration, and whether such repair can decrease seizure risk. Here we show, in a rat model of subcortical band heterotopia (SBH) generated by in utero RNAi of Dcx, that aberrantly positioned neurons can be stimulated to migrate by re-expressing Dcx after birth. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
108
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(121 citation statements)
references
References 44 publications
10
108
0
Order By: Relevance
“…Since brain injuries in extremely preterm infants might also affect the neuronal proliferation that continues after 23 GWs (21,22), the increase in the number of neurons in the white matter might have occurred in a larger scale if there were no reduction in the number of progenitor/precursor cells. The increase in the number of neurons in the white matter may also alter the cortical circuitry, as reported in the cases of intractable epilepsy (58,59), schizophrenia (60), and autism (61). As demonstrated in our present and recent studies (33) (Figure 7), the ectopic neurons in the white matter might trap axons from the contralateral hemisphere and disrupt appropriate axonal extension into the superficial layers of the overlying neocortex.…”
Section: Discussionsupporting
confidence: 78%
“…Since brain injuries in extremely preterm infants might also affect the neuronal proliferation that continues after 23 GWs (21,22), the increase in the number of neurons in the white matter might have occurred in a larger scale if there were no reduction in the number of progenitor/precursor cells. The increase in the number of neurons in the white matter may also alter the cortical circuitry, as reported in the cases of intractable epilepsy (58,59), schizophrenia (60), and autism (61). As demonstrated in our present and recent studies (33) (Figure 7), the ectopic neurons in the white matter might trap axons from the contralateral hemisphere and disrupt appropriate axonal extension into the superficial layers of the overlying neocortex.…”
Section: Discussionsupporting
confidence: 78%
“…In dendrites, αII/βIII spectrin complexes function in dendritic development, likely through interactions with ankyrin-R. jci. (17,48). The final concentrations used for transfections were 0.5 μg/μl for EGFP, 1.5 μg/μl for Sptan1 CRISPRs, 2 μg/μl for WT or mutant SPTAN, and 1 μg/μl for gephyrin-FingR-GFP.…”
Section: Discussionmentioning
confidence: 99%
“…Reelin is known to be associated with schizophrenia and bipolar disorder (Shifman et al, 2008;Goes et al, 2010;Liu et al, 2010), suggesting that Reelin is involved in higher brain functions. Moreover, we and another group recently found that supplementation of Reelin prevented the behavioral deficits related to schizophrenia and bipolar disorder (Teixeira et al, 2011;Ishii et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The coding sequence of Reelin from pCrl was inserted into pCAGGS1 containing a modified chicken ␤-actin promoter with the cytomegalovirusimmediate early enhancer (CAG) promoter (Niwa et al, 1991), kindly provided by Dr. J. Miyazaki (Osaka University), by using EcoRI and NotI sites, as previously reported . To construct CAGtandem-Tomato fluorescent protein (tdTomato), the BamH I/NotI fragment of the tdTomato vector (Clontech) was introduced into the CAG-MCS2 vector (Kawauchi et al, 2005). pCGC-Cdk5N144 ( pCGC-DN-Cdk5) was obtained as a kind gift from Dr. Toshio Oshima (Waseda University).…”
Section: Construction Of Plasmidsmentioning
confidence: 99%